Glutamate Residues In the Second Extracellular Loop of the Human A(2a) Adenosine Receptor Are Required for Ligand Recognition - KIM, JEONGHO (1996)
The A(2a) adenosine receptor, a member of the G protein-coupled receptor family, is important in the regulation of dopaminergic pathways of the brain and in platelet and cardiovascular functions. In this study, the role of extracellular loops in ligand binding to the human A(2a) receptor was explored through site-directed mutagenesis. Four glutamate/aspartate residues (Glu(151), Glu(161), Glu(169), and Asp(170)) in the second extracellular loop (E2) and a cysteine residue (Cys(262)) in the third extracellular loop (E3) were individually replaced with alanine and other amino acids. A proline residue (Pro(173)) in E2 was mutated to arginine, the homologous amino acid in A(3) receptors. The binding properties of the resultant mutant receptors were determined in transfected COS-7 cells. The mutant receptors were tagged at their amino terminus with a hemagglutinin epitope, thus allowing their detection in the plasma membrane with immunological techniques. High affinity specific binding of [(3)H]2-[4-[(2-carboxyethyl)phenyl]ethyl-amino]-5′-N-ethylcarboxamidoadenosine (15 nm) and [(3)H]8-[4-[[[[(2-aminoethyl)-amino]carbonyl]methyl]oxy]phenyl]-1,3- dipropylxanthine (4 nm), an A(2a) agonist and antagonist, respectively, was not observed with four of the mutant receptors, E(151)A, E(151)Q, E(151)D, and E(169)A, although they were well expressed at the cell surface. The E(151)A and E(169)A mutant receptors showed nearly full stimulation of adenylyl cyclase at ~10(3)-fold higher concentrations of 2-[4-[(2-carboxyethyl)phenyl]ethyl-amino]-5′-N-ethylcarboxamidoadenosine. The E(161)A mutant receptor showed an increase in affinity for the nonxanthine adenosine antagonist 9-chloro-2-(furyl)[1,2,4]triazolo[1,5-c]quinazolin-5-amine (6-fold) but not for other ligands. An E(169)Q mutant gained affinity (5–22-fold) for adenosine derivatives (agonists) substituted at N6 but not at C2 or C5′ positions. Mutant receptors D(170)K and P(173)R were similar to wild-type receptors in binding of both agonist and antagonist radioligands. A C(262)G mutant also resembled the wild-type receptor in radioligand binding, indicating that a potential disulfide bridge with another cysteine residue in proximity is not required for the structural integrity of the receptor. Our data suggest that certain amino acids in the second extracellular loop may be directly or indirectly involved in ligand binding.